Insulin Modulates Inflammatory Cytokine Release in Acute Stages and Augments Expression of Adhesion Molecules and Leukocytes in Lungs on Chronic Stages of Paracoccidioidomycosis - Casagrande, Felipe Beccaria; Ferreira, Sabrina de Souza; de Sousa, Emanuella Sarmento Alho; Guimarães, João Pedro Tôrres; Romera, Lavínia Maria Dal’Mas; Tessaro, Fernando Henrique Galvão; Almeida, Sandro Rogério de; Rodrigues, Stephen Fernandes de Paula; Martins, Joilson O. (Frontiers in Immunology, 2020)
Type 1 diabetesmellitus (T1D) is caused by partial destruction of the insulin-producing beta cells in the pancreas and is a major issue for public health care worldwide. Reduced or impaired immunological responses, which render patients more susceptible to infections, have been observed in T1D, and this dysfunction is often related to a lack of insulin in the blood. Paracoccidioidomycosis is an important systemic mycosis endemic in Latin America. To evaluate the effects of T1D on this fungal infection and the modulatory effects of insulin, we induced diabetes in C57Bl/6 male mice (alloxan, 60 mg/kg), infected the mice (Pb18, 1 x 106 cells), and treated the mice with neutral protamine Hagedorn (NPH) insulin (2 IU/600 mg/dL blood glucose). Twenty-four hours after infection, infected diabetic mice showed reduced secretion of interferon (IFN)-γ and interleukine (IL)-12 p70 compared to infected nondiabetic controls. On the 45th day of infection, infected diabetic mice presented higher IFN-γ levels, a higher tumor necrosis factor (TNF)-α:IL-10 ratio, and lower adhesion molecule expression levels than nondiabetic mice. In the in vitro experiments, alveolar macrophages from diabetic animals showed reduced phagocytic activity compared to those from control animals at 4, 12, and 24 h. In infected diabetic mice, treatment with insulin restored IL-12 p70 levels at 24 h of infection, reduced IFN-γ levels and the TNF-α:IL-10 ratio at 45 days, and restored vascular cell adhesion molecule (VCAM)-1 expression in pulmonary blood vessels, and this treatment reduced the diminished phosphorylation of extracellular signal-regulated kinases (ERK) and increased nuclear factor-kappa-B(iκb)-α and jun amino-terminal kinases (JNK) p46 levels in infected nondiabetic mice. In addition, insulin promoted increased phagocytic activity in the alveolar macrophages of diabetic mice. These data suggest that T1D mice are more susceptible to Pb18 infection and that insulin modulates this inflammation in diabetic mice by augmenting the expression of adhesion molecules and leukocytes in the lungs and by reducing chronic inflammation.